The Industrial Purchasing Decision as a Political Process - Pettigrew, A (1975)
Reports on an empirical study of the decision to purchase computers in a single firm. States it is a competitive bidding situation with several suppliers attempting to win a contract that eventually reached £3.5 million pounds. Illustrates how the politics of the firm can influence significant purchase decisions and, in particular, how gatekeepers within the firm's buying centre can structure the outcome of purchase decision in line with their position in the political process. Bases the study on a large organisation in England, in the period 1957–1968, with regard to four computer purchase decisions. Concludes that it is clear that the computer suppliers had differential access to the firm's power structure and it was also evident they had differential knowledge of its operation.